P689 Predictive transcriptional signatures associated to vedolizumab therapy response in patients with ulcerative colitis. (30th January 2023) - Camba Gómez, M; Arosa, L; Calviño-Suárez, C; Bastón-Rey, I; Ferreiro-Iglesias, R; Porto, M; Nieto, L; Domínguez-Muñoz, J E; Barreiro-de Acosta, M; Conde-Aranda, J
Abstract: Background: Vedolizumab is one of the current treatments for patients with inflammatory bowel disease (IBD). The efficacy and safety, along with its gut specificity, make this drug an appealing therapeutic option for IBD patients with moderate to severe disease. However, as observed for other biologic treatments, a significant proportion of patients do not have an initial response to vedolizumab treatment. Currently, there is a lack of reliable predictive tools for vedolizumab treatment response, although this would help to alleviate the socioeconomic costs derived from this disease. For that reason, the primary aim of this study is to show putative transcriptional signatures associated with vedolizumab treatment response. Methods: For the realization of this study, we used RNA-seq datasets from the Gene Expression Omnibus (GEO) database: GSE191328. This dataset includes samples from peripheral blood cells from responder and non-responder ulcerative colitis (UC) patients treated with vedolizumab and infliximab at baseline. Gene Set Enrichment Analysis (GSEA) was performed to compare the differential expression and the enrichment analysis was calculated using ssGSEA of the different groups under study. Results: The analysis of the transcriptome of peripheral blood cells from responder (R) and non-responder (NR) vedolizumab-treated patients at baseline revealed interesting enrichment results. We found 20 gene sets positively enriched in NR versus R and only 9 gene sets negatively enriched in the same phenotypes. In order to find vedolizumab specific transcriptional signatures, we performed a similar analysis in samples from infliximab-treated patients. After that second round of analysis, we observed that around 50% of the enriched gene sets were similar for both biological treatments. Nevertheless, several interesting biological functions such as peroxisome function, reactive oxygen function or beta-catenin signalling are specifically enriched in NR patients to vedolizumab treatment. Conclusion: Our data suggest that vedolizumab NR patients specifically show a transcriptional enrichment profile, which differs from vedolizumab R patients. Also, the comparative analysis with infliximab-treated patients reveals that those specific transcripts are modulated in response to this α4β7 integrin antibodies in peripheral blood cells. Therefore, we found a solid system to search for vedolizumab therapy predictive response markers using low invasive techniques.